Comprehensive Network Analysis Reveals Alternative Splicing-Related lncRNAs in Hepatocellular Carcinoma - Wang, Junqing; Wang, Xiuquan; Bhat, Akshay; Chen, Yixin; Xu, Keli; Mo, Yin-yuan; Yi, Song Stephen; Zhou, Yunyun (Frontiers in Genetics, 2020)
A number of recent studies have highlighted the findings that certain lncRNAs are associated with alternative splicing (AS) in tumorigenesis and progression. Although existing work showed the importance of linking certain misregulations of RNA splicing with lncRNAs, a primary concern is the lack of genome-wide comprehensive analysis for their associations. We analyzed massive RNA-seq data, quantified 198,619 isoform expressions, and found a total of 1375 AS isoforms switched between hepatocellular carcinoma (HCC) and normal liver tissue. To further predict AS-associated lncRNAs, we integrated the co-expression and epigenetic interaction networks, linking lncRNA modulators such as splicing factors, transcript factors, and miRNAs with their targeted AS genes in HCC. To model the heterogeneous networks in a single framework, we developed a multi-graphic random walk (RWMG) network method to rank the important lncRNAs. RWMG showed a good performance evaluated by ROC curve based on cross-validation and bootstrapping strategy. As a summary, we prioritized 31 AS-related lncRNAs including MALAT1 and HOXA11-AS, which have been reported before, as well as some novel lncRNAs such as DNM1P35, HAND2-AS1, and DLX6-AS1. Survival analysis further confirmed the clinical significance of identified lncRNAs.